Innovations In Assisted Reproduction Technology - Sharma, Nidhi; Chakrabarti, Sudakshina; Barak, Yona; Ellenbogen, Adrian (IntechOpen, 2020)
This book deals with all recent advances in clinical and laboratory aspects of assisted reproductive therapy (ART). It elaborates on innovations and developments in the field that have the potential to improve ART outcomes. Chapters cover such topics as newer techniques for evaluating sperm, DNA, and ovarian reserve, including proteomic analysis, sonoendocrinology, preparation and administration of platelet-rich plasma, and in vitro maturation. Authors also address the structure, function, and role of low molecular weight ligands of gonadotropins, as well as the ethical and legal aspects of ART.